The Dutch Citizen Forum on Public Reimbursement of Healthcare: A Qualitative Analysis of Opinion Change - Maarten Jansen; Rob Baltussen; Leon Bijlmakers; Marcia Tummers (International Journal of Health Policy and Management, 2022)
BackgroundA deliberative Citizen Forum ‘Choices in healthcare’ was held in the Netherlands to obtain insight into the criteria informed citizens would propose for the public reimbursement of healthcare. During 3 weekends, 24 citizens participated in evidence-informed deliberation on the basis of 8 case studies. The aim of this study was to assess how the opinions of 8 participants in the deliberative Citizens Forum changed and if so, why participants themselves believe their opinions have changed, whether participation influenced their perceived reasonableness of other participants in the forum and whether it influenced their opinions about involvement of citizens in decision-making.MethodsSemi-structured interviews were held with 8 participants before and after their participation in the Citizen Forum. Using the method of reconstructing interpretive frames opinions about the public reimbursement of healthcare were reconstructed.ResultsParticipants’ opinions changed over time; they became more aware of the complexity of decision-making and came to accept that there are limits to the available resources and accept cost as a criterion for reimbursement decisionmaking. Participants report that exchanging arguments and personal experiences with other participants made them change their initial opinions. Participants ascribed increases in the perceived reasonableness of other participants’ opinions to feelings of group-bonding and becoming more familiar with each other’s personal circumstances. Participants further believe that citizens represent an additional opinion to that of other stakeholders and believe their opinions should be considered in relation to those of other stakeholders, given they are provided with opportunities for critical discussion. ConclusionOrganized deliberation should allow for the exchange of arguments and the sharing of personal experiences which is linked to learning. On the one hand this is reflected in the uptake of new arguments and on the other hand in the revision, specification or expansion of personal argumentation. Providing opportunities for critical deliberation is key to prevent citizens from adhering to initial emotional reactions that remain unchallenged and which may no longer be supported after deliberation.